Composite film and preparation method thereof, light-emitting device and display device
By adopting a composite thin film structure in the quantum dot light emitting device, using the charge functional layer and metal particle layer of the wrinkled structure, the fluorescence attenuation problem caused by the unbalanced electron-hole injection in the quantum dot light emitting layer is solved, and the radiation recombination rate and photoelectric performance of the light emitting device are significantly improved.
Patent Information
- Application Number
- CN202311253440.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
The unbalanced electron-hole injection in the quantum dot luminescent layer causes fluorescence attenuation, affecting the performance of the light emitting device.
A composite film structure is adopted, which includes a first charge functional layer and a first metal particle layer arranged stacked, the first charge functional layer has a first pleated structure, and the second charge functional layer is arranged on one side of the first metal particle layer away from the first charge functional layer, and has a third pleated structure.
Through effective energy transfer, the radiation recombination rate of the quantum dot luminescent layer is significantly improved, the fluorescence intensity is enhanced, and the photoelectric performance of the luminescent device is improved.
Smart Images

Figure CN119730576A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of display technology, and more specifically, to a composite film and a preparation method thereof, a light-emitting device and a display device. Background Art
[0002] Colloidal quantum dots have received extensive attention and research due to their many advantages, including wide absorption, narrow emission, color purity and high quantum yield. At present, research on quantum dots at the structural level has made great progress, however, there are still many factors that hinder their application in devices; for example, the unbalanced electron-hole injection in the device leads to the accumulation of excess electrons in the quantum dot light-emitting layer, increasing the proportion of non-radiative recombination of excitons, and thus causing fluorescence attenuation of the quantum dot light-emitting layer, which in turn affects the performance of the light-emitting device. Summary of the invention
[0003] Based on this, the embodiments of the present application provide a composite film and a preparation method thereof, a light-emitting device and a display device.
[0004] In order to solve the above technical problems, the present application provides a composite film, which adopts the following technical solution:
[0005] A composite film comprises: a first charge functional layer and a first metal particle layer which are stacked; the first charge functional layer has a first wrinkle structure.
[0006] Furthermore, the composite film also includes a second charge functional layer, which is arranged on a side of the first metal particle layer away from the first charge functional layer; and the first metal particle layer has a second wrinkle structure.
[0007] Furthermore, the second charge functional layer has a third corrugated structure, and the first corrugated structure, the second corrugated structure and the third corrugated structure are stacked in sequence.
[0008] Further, the thickness of the second charge functional layer is 5nm-20nm; and / or,
[0009] The material of the second charge functional layer is selected from poly(9,9-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine), polyvinylcarbazole, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine), 4,4',4"-tri(carbazole-9-yl)triphenylamine, 4,4'-bis(9-carbazole)biphenyl, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-(1 -naphthyl)-1,1'-biphenyl-4,4'-diamine, poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid), 4,4',4'-tri(N-3-methylphenyl-Nphenylamino)triphenylamine, polyaniline, TFB, CuPc, Poly-TPD, DNTPD, TCATA, TCCA, TAPC, MCC, F4-TCNQ, HATCN, Spiro-NPB, Spiro-TPD, transition metal oxides, transition metal sulfides, transition metal tinides, doped graphene, undoped graphene and at least one of C60.
[0010] Furthermore, the material of the first metal particle layer is selected from one of aluminum and its alloys, copper and its alloys, gold and its alloys, silver and its alloys; and / or,
[0011] The thickness of the first metal particle layer is 5nm-10nm; and / or,
[0012] The first charge functional layer is a hole injection layer, the material of which is selected from glycerol-doped PEDOT:PSS; and / or,
[0013] The thickness of the first charge functional layer is 30nm-50nm.
[0014] In order to solve the above technical problems, the present application also provides a method for preparing a composite film, which adopts the following technical solution:
[0015] A method for preparing a composite film, the method comprising the following steps:
[0016] providing a preform, the preform comprising a corrugated template and a first charge functional layer;
[0017] Processing the first charge functional layer by using a wrinkle template so that the first charge functional layer has a first wrinkle structure;
[0018] A first metal particle layer is disposed on the first charge functional layer.
[0019] Further, the step of providing a preform, wherein the preform includes a pleated template and a first charge functional layer, specifically includes:
[0020] Obtaining a substrate;
[0021] preparing a polymer template on the substrate;
[0022] A second metal particle layer is arranged on the polymer template, wherein the second metal particle layer has a different thermal expansion coefficient from the polymer template, so that the second metal particle layer is bent, wherein the material of the second metal particle layer is selected from one of aluminum, titanium, copper, nickel and gold;
[0023] separating the polymer template having the second metal particle layer from the substrate to obtain a wrinkled template; and / or,
[0024] The step of using the corrugated template to process the first charge functional layer so that the first charge functional layer has a first corrugated structure specifically includes:
[0025] The corrugated template is transferred onto the first charge functional layer, so that the first charge functional layer has a first corrugated structure.
[0026] Furthermore, the step of preparing a polymer template on the substrate specifically includes:
[0027] Providing a polymer material, and mixing the polymer material with an adhesive in a preset ratio to obtain a mixed solution, wherein the polymer material is at least one of polydimethylsiloxane, polymethyl methacrylate, polyimide, and photoresist;
[0028] The mixed solution is stirred at a first temperature for a first time, and vacuum dried at room temperature for a second time to discharge bubbles;
[0029] The mixed solution from which bubbles are expelled is uniformly cast on the substrate, and is cured at a second temperature.
[0030] In order to solve the above technical problems, the embodiment of the present application further provides a light emitting device, which adopts the following technical solution:
[0031] A light emitting device, comprising: a first electrode layer, a second electrode layer, a quantum dot light emitting layer, and the composite film as described above;
[0032] The quantum dot light-emitting layer is arranged between the first electrode layer and the second electrode layer; the composite film is arranged between the first electrode layer and the quantum dot light-emitting layer, and the first metal particle layer is arranged close to the quantum dot light-emitting layer.
[0033] Further, the quantum dot light-emitting layer has a fourth wrinkle structure; and / or,
[0034] The first electrode layer and the second electrode layer are each selected from one or more of a metal electrode, a silicon-carbon electrode, a doped or undoped metal oxide electrode and a composite electrode; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca and Mg; the material of the silicon-carbon electrode is selected from at least one of silicon, graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZ O, MZO and AMO; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or,
[0035] The material of the quantum dot light-emitting layer includes at least one of a single structure quantum dot and a core-shell structure quantum dot, and the material of the single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, Cd At least one of dZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSS e, SnPbSeTe and SnPbSTe, wherein the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs s, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the core of the quantum dots of the core-shell structure includes any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure includes CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS, ZnS and at least one of the above-mentioned single-structure quantum dots; and / or,
[0036] The light-emitting device further comprises an electronic functional layer, wherein the electronic functional layer comprises an electron injection layer and / or an electron transport layer. When the electronic functional layer comprises two layers, the electron injection layer and the electron transport layer; the electron transport layer is arranged close to one side of the quantum dot light-emitting layer, and the electron injection layer is arranged away from one side of the quantum dot light-emitting layer; wherein the material of the electron transport layer is selected from at least one of doped inorganic nanocrystals, undoped inorganic nanocrystals, and organic electron transport materials, and the undoped inorganic nanocrystals are selected from ZnO, TiO2, SnO2, Al2O3, GaO, Ga2O3, ZrO2, Fe2O3, CrO3, WO3, CdO, Cu O, MoO2, ZnS, ZnSe, CdS, InP, GaP, LiF, LiF / Yb, MgP, MgF2, Ga2O3, Cs2CO3, Rb2CO3, RbBr; the doped inorganic nanocrystals include a second non-doped inorganic nanocrystal and a doping element, and the second non-doped inorganic nanocrystals are selected from ZnO, TiO2, SnO2, Al2O3, GaO, Ga2O3, ZrO2, Fe2O3, CrO3, WO3, CdO, CuO, MoO2, ZnS, ZnSe, CdS, InP, GaP, LiF, LiF / Yb, MgP, MgF2, G a2O3, Cs2CO3, Rb2CO3, RbBr, the doping element is selected from one or more of Mg, Ca, Li, Ga, Al, Co, Mn; the organic electron transport material is selected from [6,6]-phenyl C71 butyric acid methyl ester, [6,6]-phenyl C61 butyric acid methyl ester, organic fullerene materials, 2-ethyl-1-(4-(10-(2-naphthyl)-9-anthracenyl)phenyl)-1H-benzimidazole, 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 3,3'-[5'-[3-(3-pyridyl)phenyl](TmPyPb), 4,6- Bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine (B3PYMPM), phenylpyridinium beryllium (Bepp2), 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 3-(biphenyl-4-yl)-5-(4-tert-butylphenyl)-4-phenyl-4H-1,2,4-triazole (TAZ), 1,3,5-tri[(3-pyridyl)-3-phenyl]benzene (TmPyPb), tris-(8-hydroxyquinoline)aluminum (Alq3), 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP), 4,7-diphenyl-1,10-phenanthroline (Bphen);
[0037] The material of the electron injection layer is selected from at least one of LiF, Yb, LiF / Yb, MgP, MgF2, Al2O3, Ga2O3, ZnO, Cs2CO3, Rb2CO3, and RbBr.
[0038] In order to solve the above technical problems, the embodiment of the present application further provides a display device, which adopts the following technical solution:
[0039] A display device comprises the composite film as described above, or comprises the composite film prepared by the composite film preparation method as described above, or comprises the light-emitting device as described above.
[0040] Compared with the prior art, the embodiments of the present application have the following beneficial effects: when the resonance absorption peak of the metal nanoparticles in the first metal particle layer effectively overlaps with the emission peak of the quantum dots, the radiation recombination rate of the quantum dot light-emitting layer is significantly improved through effective energy transfer. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the scheme of the present application, a brief introduction is given below to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0042] Figure 1 is a schematic diagram of an embodiment of a composite film of the present application;
[0043] Figure 2 is a flow chart of an embodiment of a composite film preparation method of the present application;
[0044] Figure 3 is a schematic diagram of an embodiment of a light emitting device of the present application;
[0045] Figure 4 This is an AFM image of an example wrinkle structure.
[0046] Figure numerals: 1. first electrode layer; 2. composite film; 21. first charge functional layer; 211. first wrinkle surface; 22. first metal particle layer; 221. second wrinkle surface; 23. second charge functional layer; 231. third wrinkle surface; 3. quantum dot light-emitting layer; 31. fourth wrinkle surface; 4. electron transport layer; 5. second electrode layer. DETAILED DESCRIPTION
[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of this application; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned drawings are intended to cover non-exclusive inclusions. The terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects, not to describe a specific order.
[0048] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0049] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings.
[0050] For ease of understanding, the terms mentioned in the specific implementation are first explained below:
[0051] SPR (Surface Plasmon Resonance): When a light wave is incident on the metal / medium interface, an oscillating electric field is generated on the metal surface. The free electrons on the metal surface will oscillate collectively under the action of the electric field. The electromagnetic wave and the free electrons on the metal surface couple to produce a near-field electromagnetic wave that propagates along the metal surface. If the frequency of the incident photon is consistent with the oscillation frequency of the electron, resonance will occur.
[0052] LSP (local Surface Plasmons): When metal is made into nanoparticles, local surface plasmons will be generated on the surface of the metal nanoparticles.
[0053] LSPR (full name: localized Surface Plasmon Resonance): When light is incident on nanoparticles made of metal, if the frequency of the incident photons matches the overall vibration frequency of the metal nanoparticles or metal conduction electrons, the nanoparticles or metals will have a strong absorption effect on the photon energy, and localized surface plasmon resonance will occur, and a strong resonance absorption peak will appear in the spectrum.
[0054] The present application embodiment provides a composite film 2, such as Figure 1 As shown, the composite film 2 includes: a first charge functional layer 21 and a first metal particle layer 22 which are stacked; the first charge functional layer 21 has a first wrinkled structure.
[0055] See also Figure 4 , Figure 4 This is an AFM (atomic force microscope) image of an example wrinkle structure.
[0056] In this embodiment, the composite film 2 is applied to a light-emitting device, specifically a quantum dot light-emitting device, and the first metal particle layer 22 is arranged close to the quantum dot light-emitting layer of the quantum dot light-emitting device; since the first charge functional layer 21 has a first wrinkled structure, and the first metal particle layer 22 is arranged on the first charge functional layer 21, the surface of the first metal particle layer 22 adjacent to the first charge functional layer 21 is no longer flattened; in a resonant state, a strong local electromagnetic field is formed around the metal nanoparticles in the first metal particle layer 22, and eventually the excitons in the quantum dot light-emitting layer overlap with the local electromagnetic field of the LSPR of the metal nanoparticles in the first metal particle layer 22, causing a local plasma coupling effect, so as to significantly improve the radiation recombination rate through effective energy transfer; this embodiment improves the problem of low luminescence efficiency of the device by enhancing the fluorescence intensity of the quantum dot light-emitting layer.
[0057] In this embodiment, the plasma resonance characteristics of the metal nanoparticles in the first metal particle layer 22 are affected by the geometric structure, size, dielectric properties and the surrounding physical environment. Therefore, in this embodiment, the geometric structure of the first metal particle layer 22 can be adjusted by the first pleated structure to regulate the resonance absorption peak of the metal nanoparticles so that the resonance absorption peak can effectively overlap with the emission peaks of the red, green and blue primary color quantum dots, so that this embodiment can be applied to red, green and blue primary color quantum dot light-emitting devices, and the fluorescence intensity of the quantum dots can be enhanced through the localized surface plasma resonance effect of the first metal particle layer 22, and the radiation recombination rate of the quantum dot light-emitting layer can be increased, so as to improve the photoelectric performance of the red, green and blue primary color quantum dot light-emitting devices.
[0058] In the present embodiment, a first metal particle layer 22 is provided on the first charge functional layer 21 to form a composite film 2, instead of directly adding metal nanoparticles into the quantum dot light-emitting layer; the purpose is to provide a suitable distance between the metal nanoparticles and the fluorescent molecules. When the metal nanoparticles and the fluorescent molecules are close to each other, although the intensity of the excited electromagnetic field is strong, more energy is transferred to the metal nanoparticles in a non-radiative form, which makes the negative impact caused by the non-radiative loss stronger than the enhancement effect of the exciting electromagnetic field, causing fluorescence quenching; therefore, in the present embodiment, the fluorescence intensity of the quantum dots can be enhanced, the radiation recombination rate of the light-emitting layer can be increased, and the negative impact caused by the non-radiative loss can be prevented from being stronger than the enhancement effect of the exciting electromagnetic field.
[0059] like Figure 1 As shown, further, the composite film 2 also includes a second charge functional layer 23, and the second charge functional layer 23 is arranged on a side of the first metal particle layer 22 away from the first charge functional layer 21; the first metal particle layer 22 has a second fold structure.
[0060] In this embodiment, when the composite film 2 is applied to a quantum dot light-emitting device, the second charge functional layer 23 is arranged close to the quantum dot light-emitting layer, and the surface of the second charge functional layer 23 adjacent to the first metal particle layer 22 is no longer flattened, further causing the excitons in the quantum dot light-emitting layer to overlap with the local electromagnetic field of the LSPR of the metal nanoparticles in the first metal particle layer 22.
[0061] In this embodiment, the morphology and size of the first metal particle layer 22 are adjusted by the first fold structure to control the resonance absorption peak of the first metal particle layer 22 .
[0062] In this embodiment, when the composite film 2 is applied to a quantum dot light-emitting device, the second charge functional layer 23 is arranged close to the quantum dot light-emitting layer. The second charge functional layer 23 can adjust the distance between the first metal particle layer 22 and the quantum dot light-emitting layer to avoid the metal nanoparticles and the fluorescent molecules being too close. At the same time, the thickness of the second charge functional layer 23 can also be adjusted to avoid the metal nanoparticles and the fluorescent molecules being too far apart, to avoid the interaction between the metal nanoparticles and the fluorescent molecules being weak, and to convert it into a far-field scattering optical enhancement form.
[0063] Furthermore, the material of the first metal particle layer 22 is selected from one of aluminum and its alloys, copper and its alloys, gold and its alloys, and silver and its alloys.
[0064] In this embodiment, the absorption spectra of aluminum and its alloys, copper and its alloys, gold and its alloys, and silver and its alloys are distributed in the visible light region to generate a surface plasmon resonance effect in a specific size and medium environment.
[0065] Furthermore, the thickness of the first metal particle layer 22 is 5 nm-10 nm.
[0066] In some optional implementations of this embodiment, the thickness of the first metal particle layer 22 is any one of 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, etc., or in a range between any two of them.
[0067] Furthermore, the first charge functional layer 21 is a hole injection layer, and the material thereof is selected from glycerol-doped PEDOT:PSS.
[0068] PEDOT:PSS solution is an aqueous solution without an obvious glass transition temperature and has a relatively high viscosity of 120,000 mPa.s after spin coating. When preparing the first wrinkled surface 211, a stamping method is adopted (see below for details), and the PEDOT:PSS solution does not have the fluidity required for stamping and cannot be directly stamped. Therefore, in this embodiment, propylene glycol is doped into the PEDOT:PSS solution to improve its plasticity after film formation.
[0069] Specifically, the material of the first charge functional layer 21 is selected from PEDOT:PSS doped with 3% glycerol.
[0070] Furthermore, the thickness of the first charge functional layer 21 is 30nm-50nm.
[0071] In some optional implementations of this embodiment, the thickness of the first charge functional layer 21 is any one of 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, etc., or in the range between any two of them.
[0072] Furthermore, the second charge functional layer 23 has a third corrugated structure, and the first corrugated structure, the second corrugated structure, and the third corrugated structure are stacked in sequence.
[0073] In this embodiment, when the composite film 2 is applied to a quantum dot light-emitting device, the second charge functional layer 23 is arranged close to the quantum dot light-emitting layer, and the surface of the quantum dot light-emitting layer adjacent to the second charge functional layer 23 is no longer flattened, further causing the excitons in the quantum dot light-emitting layer to overlap with the local electromagnetic field of the LSPR of the metal nanoparticles in the first metal particle layer 22.
[0074] In this embodiment, the morphology and size of the first metal particle layer 22 are adjusted by the first pleated structure to control the resonance absorption peak of the first metal particle layer 22, and the first pleated structure, the second pleated structure, and the third pleated structure are stacked in sequence to maintain the resonance absorption peak of the first metal particle layer 22.
[0075] Furthermore, the thickness of the second charge functional layer 23 is 5 nm-20 nm.
[0076] In some optional implementations of this embodiment, the thickness of the second charge functional layer 23 is any one of 5 nm, 10 nm, 15 nm, 20 nm, etc., or in a range between any two of them.
[0077] Further, the material of the second charge functional layer is selected from poly (9,9-dioctylfluorene-co-N-(4-butylphenyl) diphenylamine), polyvinyl carbazole, poly (N,N'-bis (4-butylphenyl) -N,N'-bis (phenyl) benzidine), poly (9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine), 4,4',4"-tri (carbazole-9-yl) triphenylamine, 4,4'-bis (9-carbazole) biphenyl, N,N'-diphenyl-N,N'-bis (3-methylphenyl) -1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-bis (3-methylphenyl) -1,1'-biphenyl-4,4'-diamine. -(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid), 4,4',4'-tri(N-3-methylphenyl-Nphenylamino)triphenylamine, polyaniline, TFB, CuPc, Poly-TPD, DNTPD, TCATA, TCCA, TAPC, MCC, F4-TCNQ, HATCN, Spiro-NPB, Spiro-TPD, transition metal oxides, transition metal sulfides, transition metal tinides, doped graphene, undoped graphene and at least one of C60.
[0078] The present application also provides a method for preparing a composite film, such as Figure 2 As shown, the method comprises the following steps:
[0079] S11, providing a preform, wherein the preform comprises a pleated template and a first charge functional layer;
[0080] S12, using the corrugation template to process the first charge functional layer so that the first charge functional layer has a first corrugation structure;
[0081] S13, disposing a first metal particle layer on the first charge functional layer.
[0082] In this embodiment, a preform is first provided, the preform includes a corrugated template and a first charge functional layer. It should be noted that the corrugated template and the first charge functional layer are independent of each other. Then, the first charge functional layer is processed by using the corrugated template so that the first charge functional layer has a first corrugated structure. Finally, a first metal particle layer is provided on the first charge functional layer.
[0083] In this embodiment, the prepared composite film is applied to a light-emitting device, specifically a quantum dot light-emitting device, and the first metal particle layer is arranged close to the quantum dot light-emitting layer of the quantum dot light-emitting device; the first charge functional layer is processed by using a corrugated template so that the first charge functional layer has a first corrugated structure; the first metal particle layer is arranged on the first charge functional layer so that the surface of the first metal particle layer adjacent to the first charge functional layer is no longer flattened, thereby ultimately causing the excitons in the quantum dot light-emitting layer to overlap with the local electromagnetic field of the LSPR of the metal nanoparticles in the first metal particle layer, causing a localized plasma coupling effect, thereby significantly improving the radiative recombination rate through effective energy transfer.
[0084] In this embodiment, the first wrinkle structure is determined by the wrinkle template. Therefore, this embodiment can regulate the resonance absorption peak of the metal nanoparticles through the wrinkle template so that its resonance absorption peak can effectively overlap with the emission peaks of the red, green and blue primary color quantum dots, so that this embodiment can be applied to red, green and blue primary color quantum dot light-emitting devices.
[0085] Furthermore, in the step S11, providing a preform, wherein the preform includes a pleated template and a first charge functional layer, specifically includes:
[0086] Obtaining a substrate;
[0087] preparing a polymer template on the substrate;
[0088] A second metal particle layer is arranged on the polymer template, wherein the second metal particle layer has a different thermal expansion coefficient from the polymer template, so that the second metal particle layer is bent, wherein the material of the second metal particle layer is selected from one of aluminum, titanium, copper, nickel and gold;
[0089] The polymer template with the second metal particle layer is separated from the substrate to obtain a wrinkled template.
[0090] In this embodiment, first, a substrate is obtained; then, a polymer template is prepared on the substrate; then, a second metal particle layer is set on the polymer template. Since the second metal particle layer and the polymer template have different thermal expansion coefficients, the difference in thermal expansion coefficients between the second metal particle layer and the polymer template causes the compressive stress to be automatically released, causing the second metal particle layer to bend; finally, the polymer template with the second metal particle layer is separated from the substrate to obtain a wrinkled template.
[0091] Furthermore, the step S12, using the corrugated template to process the first charge functional layer so that the first charge functional layer has a first corrugated structure, specifically includes:
[0092] The corrugated template is transferred onto the first charge functional layer, so that the first charge functional layer has a first corrugated structure.
[0093] In this embodiment, the first charge functional layer can be quickly provided with the first wrinkled structure by transfer printing.
[0094] Furthermore, the substrate is a glass substrate.
[0095] Furthermore, the step of preparing a polymer template on the substrate specifically includes:
[0096] Providing a polymer material, and mixing the polymer material with an adhesive in a preset ratio to obtain a mixed solution, wherein the polymer material is at least one of polydimethylsiloxane, polymethyl methacrylate, polyimide, and photoresist;
[0097] The mixed solution is stirred at a first temperature for a first time, and vacuum dried at room temperature for a second time to discharge bubbles;
[0098] The mixed solution from which bubbles are expelled is uniformly cast on the substrate, and is cured at a second temperature.
[0099] Furthermore, the preset ratio is (5:1)-(10:1).
[0100] In some optional implementations of this embodiment, the preset ratio is any one of 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc., or a range between any two of them.
[0101] Furthermore, the first temperature is 20°C-30°C.
[0102] In some optional implementations of this embodiment, the first temperature is any one of 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, etc., or a range between any two of them.
[0103] Furthermore, the first duration is 20 minutes to 1 hour.
[0104] In some optional implementations of this embodiment, the first duration is any one of 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 1 h, etc., or a range between any two of them.
[0105] Furthermore, the second duration is 0.5h-2h.
[0106] In some optional implementations of this embodiment, the first duration is any one of 0.5h, 0.8h, 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, etc., or a range between any two of them.
[0107] Furthermore, the second temperature is 50°C-100°C.
[0108] In some optional implementations of this embodiment, the first temperature is any one of 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc., or a range between any two of them.
[0109] Furthermore, the step of providing a second metal particle layer on the polymer template specifically comprises:
[0110] The second metal particle layer is evaporated on the polymer template.
[0111] Specifically, the thickness of the second metal particle layer is 5nm-100nm.
[0112] In some optional implementations of this embodiment, the thickness of the second metal particle layer is any one of 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, etc., or a range between any two of them.
[0113] Furthermore, before the step of separating the polymer template from the substrate, the method further comprises:
[0114] The second metal particle layer is cleaned.
[0115] Specifically, polydimethylsiloxane (PDMS) and an adhesive are mixed in a ratio of 10:1 to obtain a mixed solution; the mixed solution is stirred at room temperature 25°C for 30 minutes, and then placed in a vacuum drying oven for 1 hour, and taken out after the bubbles are completely discharged; the mixed solution with bubbles discharged is uniformly cast on a glass substrate, and placed in a vacuum drying oven at 80°C for curing to obtain a polymer template. A 10nm thick metal aluminum layer (i.e., a second metal particle layer) is evaporated on the PDMS polymer template, and wrinkles are formed by using the different thermal expansion coefficients of the second metal particle layer and the PDMS polymer template, and then the wrinkles of the second metal particle layer are cleaned; finally, the polymer template with the second metal particle layer is peeled off from the glass substrate to obtain a wrinkle template.
[0116] The present application also provides a light emitting device, such as Figure 3 As shown, the light-emitting device includes: a first electrode layer 1, a second electrode layer 5, a quantum dot light-emitting layer 3, and the composite film 2 as described above; the quantum dot light-emitting layer 3 is arranged between the first electrode layer 1 and the second electrode layer 5; the composite film 2 is arranged between the first electrode layer 1 and the quantum dot light-emitting layer 3, and the first metal particle layer 22 is arranged close to the quantum dot light-emitting layer 3.
[0117] In this embodiment, a composite film 2 is arranged in the light-emitting device, and the first charge functional layer 21 in the composite film 2 has a first wrinkled structure, and the first metal particle layer 22 is arranged on the first charge functional layer 21, so that the surface of the first metal particle layer 22 adjacent to the first charge functional layer 21 is no longer flattened; in a resonant state, a strong local electromagnetic field is formed around the metal nanoparticles in the first metal particle layer 22; in this embodiment, the first metal particle layer 22 is arranged close to the quantum dot light-emitting layer 3, so that the excitons in the quantum dot light-emitting layer 3 overlap with the local electromagnetic field of the LSPR of the metal nanoparticles in the first metal particle layer 22, causing a local plasma coupling effect, so as to significantly improve the radiation recombination rate through effective energy transfer.
[0118] In this embodiment, the plasma resonance characteristics of the metal nanoparticles in the first metal particle layer 22 are affected by the geometric structure, size, dielectric properties and the surrounding physical environment. Therefore, in this embodiment, the geometric structure of the first metal particle layer 22 can be adjusted by the first pleated structure to regulate the resonance absorption peak of the metal nanoparticles so that the resonance absorption peak can effectively overlap with the emission peaks of the red, green and blue primary color quantum dots, so that this embodiment can be applied to red, green and blue primary color quantum dot light-emitting devices, and the fluorescence intensity of the quantum dots can be enhanced through the localized surface plasma resonance effect of the first metal particle layer 22, and the radiation recombination rate of the quantum dot light-emitting layer can be increased, so as to improve the photoelectric performance of the red, green and blue primary color quantum dot light-emitting devices.
[0119] Furthermore, a second charge functional layer 23 is disposed between the quantum dot light-emitting layer 3 and the first metal particle layer 22 .
[0120] Furthermore, the quantum dot light-emitting layer 3 has a fourth corrugated structure, and the first corrugated structure, the second corrugated structure, the third corrugated structure and the fourth corrugated structure are stacked in sequence.
[0121] In this embodiment, the quantum dot light-emitting layer 3 has a fourth corrugated structure to improve the light extraction efficiency of the device; the morphology and size of the first metal particle layer 22 are adjusted by the first corrugated structure to control the resonance absorption peak of the first metal particle layer 22, and the first corrugated structure, the second corrugated structure, the third corrugated structure and the fourth corrugated structure are stacked in sequence to maintain the resonance absorption peak of the first metal particle layer 22.
[0122] Furthermore, the first electrode layer 1 and the second electrode layer 5 are each selected from one or more of a metal electrode, a silicon-carbon electrode, a doped or undoped metal oxide electrode and a composite electrode; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca and Mg; the material of the silicon-carbon electrode is selected from at least one of silicon, graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, At least one of GZO, IZO, MZO and AMO; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2.
[0123] Furthermore, the first electrode layer 1 is an anode.
[0124] Furthermore, the thickness of the first electrode layer 1 is 10nm-150nm.
[0125] In some optional implementations of this embodiment, the thickness of the first electrode layer 1 is any one of 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, etc., or a range between any two of them.
[0126] Furthermore, the second electrode layer 5 is a cathode.
[0127] Furthermore, the second electrode layer 5 has a thickness of 10 nm-200 nm.
[0128] In some optional implementations of this embodiment, the thickness of the second electrode layer 5 is any one of 10 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, etc., or a range between any two of them.
[0129] Further, the material of the quantum dot light-emitting layer 3 includes at least one of a single structure quantum dot and a core-shell structure quantum dot, and the material of the single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZ At least one of CdNSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, wherein the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, S At least one of nPbSSe, SnPbSeTe and SnPbSTe, the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, Ga At least one of InNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the core of the core-shell structured quantum dots includes any one of the above-mentioned single-structure quantum dots, and the shell material of the core-shell structured quantum dots includes CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS, ZnS and at least one of the above-mentioned single-structure quantum dots.
[0130] Furthermore, the thickness of the quantum dot light-emitting layer 3 is 20nm-40nm.
[0131] In some optional implementations of this embodiment, the thickness of the quantum dot light-emitting layer 3 is any one of 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, etc., or in the range between any two of them.
[0132] Furthermore, the light-emitting device further comprises an electronic functional layer, wherein the electronic functional layer comprises an electron injection layer and / or an electron transport layer 4. When the electronic functional layer comprises two layers, the electron injection layer and the electron transport layer 4; the electron transport layer 4 is arranged close to the side of the quantum dot light-emitting layer 3, and the electron injection layer is arranged away from the side of the quantum dot light-emitting layer 3; wherein the material of the electron transport layer 4 is selected from at least one of doped inorganic nanocrystals, undoped inorganic nanocrystals, and organic electron transport materials, and the undoped inorganic nanocrystals are selected from ZnO, TiO2, SnO2, Al2O3, GaO, Ga2O3, ZrO2, Fe2O3, CrO3, W O3, CdO, CuO, MoO2, ZnS, ZnSe, CdS, InP, GaP, LiF, LiF / Yb, MgP, MgF2, Ga2O3, Cs2CO3, Rb2CO3, RbBr; the doped inorganic nanocrystals include a second non-doped inorganic nanocrystal and a doping element, and the second non-doped inorganic nanocrystals are selected from ZnO, TiO2, SnO2, Al2O3, GaO, Ga2O3, ZrO2, Fe2O3, CrO3, WO3, CdO, CuO, MoO2, ZnS, ZnSe, CdS, InP, GaP, LiF, LiF / Yb, MgP, MgF2, Ga2O3, Cs2CO3, Rb2CO3, RbBr; the doped inorganic nanocrystals include a second non-doped inorganic nanocrystal and a doping element, and the second non-doped inorganic nanocrystals are selected from ZnO, TiO2, SnO2, Al2O3, GaO, Ga2O3, ZrO2, Fe2O3, CrO3, WO3, CdO, CuO, MoO2, ZnS, ZnSe, CdS, InP, GaP, LiF, LiF / Yb, MgP, One or more of MgF2, Ga2O3, Cs2CO3, Rb2CO3, and RbBr, wherein the doping element is selected from one or more of Mg, Ca, Li, Ga, Al, Co, and Mn; the organic electron transport material is selected from [6,6]-phenyl C71 butyric acid methyl ester, [6,6]-phenyl C61 butyric acid methyl ester, organic fullerene materials, 2-ethyl-1-(4-(10-(2-naphthyl)-9-anthracenyl)phenyl)-1H-benzimidazole, 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 3,3'-[5'-[3-(3-pyridyl)phenyl](TmPyPb), 4 ,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine (B3PYMPM), phenylpyridinium beryllium (Bepp2), 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 3-(biphenyl-4-yl)-5-(4-tert-butylphenyl)-4-phenyl-4H-1,2,4-triazole (TAZ), 1,3,5-tri[(3-pyridyl)-3-phenyl]benzene (TmPyPb), tris-(8-hydroxyquinoline)aluminum (Alq3), 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP), 4,7-diphenyl-1,10-phenanthroline (Bphen).
[0133] Furthermore, the material of the electron injection layer is selected from at least one of LiF, Yb, LiF / Yb, MgP, MgF2, Al2O3, Ga2O3, ZnO, Cs2CO3, Rb2CO3, and RbBr.
[0134] Furthermore, the thickness of the electron transport layer 4 is 20nm-50nm.
[0135] In some optional implementations of this embodiment, the thickness of the electron transport layer 4 is any one of 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, etc., or in the range between any two of them.
[0136] An embodiment of the present application further provides a display device, comprising the composite film as described above, or comprising a composite film prepared by the composite film preparation method as described above, or comprising a light-emitting device as described above.
[0137] In this embodiment, the first charge functional layer 21 has a first wrinkled structure, and the first metal particle layer 22 is arranged on the first charge functional layer 21, so that the surface of the first metal particle layer 22 adjacent to the first charge functional layer 21 is no longer flattened; in a resonant state, a strong local electromagnetic field is formed around the metal nanoparticles in the first metal particle layer 22, and finally the excitons in the quantum dot light-emitting layer overlap with the local electromagnetic field of the LSPR of the metal nanoparticles in the first metal particle layer 22, causing a local plasma coupling effect, so as to significantly improve the radiation recombination rate through effective energy transfer; this embodiment improves the problem of low luminescence efficiency of the device by enhancing the fluorescence intensity of the quantum dot light-emitting layer.
[0138] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present invention are described in detail as follows:
[0139] Example 1
[0140] Mix polydimethylsiloxane (PDMS) and adhesive in a ratio of 10:1 to obtain a mixed solution; stir the mixed solution at room temperature 25°C for 30 minutes, then put it in a vacuum drying oven for 1 hour, and take it out after the bubbles are completely discharged; cast the mixed solution with bubbles discharged evenly on a glass substrate, and put it in a vacuum drying oven at 80°C for curing to obtain a polymer template. Evaporate a 7nm thick metal aluminum layer (i.e., the second metal particle layer) on the PDMS polymer template, and use the different thermal expansion coefficients of the second metal particle layer and the PDMS polymer template to form wrinkles, and then clean the wrinkles of the second metal particle layer; finally, peel the polymer template with the second metal particle layer from the glass substrate to obtain a wrinkle template;
[0141] Providing an ITO anode substrate (i.e., the first electrode layer), cleaning the ITO anode substrate, and then treating it under UV conditions for 15 minutes to increase its work function and wettability; then spin-coating a 50 nm thick PEDOT:PSS (doped with 3% propylene glycol) on the treated ITO anode substrate to obtain a first charge functional layer;
[0142] Using traditional nanoimprinting technology, the wrinkle template is transferred to the first charge functional layer to make the first charge functional layer have a first wrinkle structure; 8nm thick metal Au (i.e., the first metal particle layer) is deposited on the first charge functional layer and baked at 150°C for 20 minutes in an air atmosphere; then TFB is spin-coated on the first metal particle layer as a second charge functional layer with a thickness of 30nm, and then baked at 160°C for 30 minutes in a nitrogen environment; then 15nm thick blue light QDs ink is spin-coated on the second charge functional layer and baked at 100°C for 10 minutes to obtain a blue light quantum dot luminescent layer; then a 30nm thick modified ZnO electron transport layer is spin-coated and annealed at 100°C for 10 minutes; then 100nm thick Al is vacuum evaporated to obtain a second electrode layer; finally, it is packaged and annealed at 100°C for 30 minutes.
[0143] Example 2
[0144] The difference from Example 1 is that: a metal Au layer (ie, a second metal particle layer) with a thickness of 8 nm is evaporated on the PDMS polymer template; and a green light quantum dot luminescent layer is prepared on the second charge functional layer.
[0145] Example 3
[0146] The difference from Example 1 is that: a metal Au layer (ie, a second metal particle layer) with a thickness of 9 nm is evaporated on the PDMS polymer template; and a red light quantum dot luminescent layer is prepared on the second charge functional layer.
[0147] Example 4
[0148] The difference from Example 1 is that metal Cu (ie, the first metal particle layer) with a thickness of 8 nm is deposited on the first charge functional layer.
[0149] Example 5
[0150] The difference from Example 1 is that: metal Cu with a thickness of 8 nm (ie, the first metal particle layer) is deposited on the first charge functional layer; and a green light quantum dot luminescent layer is prepared on the second charge functional layer.
[0151] Example 6
[0152] The difference from Example 1 is that: metal Cu with a thickness of 8 nm (ie, the first metal particle layer) is deposited on the first charge functional layer; and a red light quantum dot luminescent layer is prepared on the second charge functional layer.
[0153] Example 7
[0154] The difference from Example 1 is that: metal Al (ie, the first metal particle layer) with a thickness of 8 nm is deposited on the first charge functional layer.
[0155] Example 8
[0156] The difference from Example 1 is that: metal Al (ie, the first metal particle layer) with a thickness of 8 nm is deposited on the first charge functional layer; and a green light quantum dot luminescent layer is prepared on the second charge functional layer.
[0157] Example 9
[0158] The difference from Example 1 is that: metal Al (ie, the first metal particle layer) with a thickness of 8 nm is deposited on the first charge functional layer; and a red light quantum dot luminescent layer is prepared on the second charge functional layer.
[0159] Example 10
[0160] The difference from Example 1 is that metal Ag (ie, the first metal particle layer) with a thickness of 8 nm is deposited on the first charge functional layer.
[0161] Embodiment 11
[0162] The difference from Example 1 is that: metal Ag with a thickness of 8 nm (ie, the first metal particle layer) is deposited on the first charge functional layer; and a green light quantum dot luminescent layer is prepared on the second charge functional layer.
[0163] Example 12
[0164] The difference from Example 1 is that: metal Ag with a thickness of 8 nm (ie, the first metal particle layer) is deposited on the first charge functional layer; and a red light quantum dot luminescent layer is prepared on the second charge functional layer.
[0165] Comparative Example 1
[0166] Providing an ITO anode substrate (i.e., a first electrode layer), cleaning the ITO anode substrate, and then treating it under UV conditions for 15 minutes to increase its work function and wettability; then spin coating a 50 nm thick PEDOT:PSS on the treated ITO anode substrate to obtain a first charge functional layer;
[0167] TFB was spin-coated on the first charge functional layer as the second charge functional layer with a thickness of 30 nm, and then baked at 160°C for 30 min in a nitrogen environment; then a 15 nm thick blue light QDs ink was spin-coated on the second charge functional layer and baked at 100°C for 10 min to obtain a blue light quantum dot luminescent layer; then a 30 nm thick modified ZnO electron transport layer was spin-coated and annealed at 100°C for 10 min; then a 100 nm thick Al was vacuum evaporated to obtain a second electrode layer; finally, it was packaged and annealed at 100°C for 30 min.
[0168] Comparative Example 2
[0169] The difference from Comparative Example 1 is that a green light quantum dot luminescent layer is prepared on the second charge functional layer.
[0170] Comparative Example 3
[0171] The difference from Comparative Example 1 is that a red light quantum dot light-emitting layer is prepared on the second charge functional layer.
[0172] Experimental test analysis: The light emitting devices prepared in Examples 1 to 12 and Comparative Examples 1 to 3 were subjected to experimental test analysis. The analysis results are shown in Table 1.
[0173] Table 1
[0174]
[0175]
[0176] Among them, Voltage (v) refers to the voltage of the light-emitting device; CEmax (cd / A) @ 1000nit refers to the maximum current efficiency of the light-emitting device; EQE% @ 1000nit refers to the external quantum efficiency of the light-emitting device.
[0177] It can be seen from Table 1 that the maximum current efficiency and external quantum efficiency of the blue light emitting devices prepared in Examples 1, 4, 7, and 10 are better than those in Comparative Example 1; the maximum current efficiency and external quantum efficiency of the green light emitting devices prepared in Examples 2, 5, 8, and 11 are better than those in Comparative Example 2; the maximum current efficiency and external quantum efficiency of the red light emitting devices prepared in Examples 3, 6, 9, and 12 are better than those in Comparative Example 3.
[0178] Specifically, the difference between Examples 1 to 12 and Comparative Examples 1 to 3 is that a composite film is applied to the light-emitting devices of Examples 1 to 12, and the first charge functional layer in the composite film has a first wrinkle structure, and the first metal particle layer is arranged on the first charge functional layer, so that the surface of the first metal particle layer adjacent to the first charge functional layer is no longer flattened, and in the resonant state, a strong local electromagnetic field is formed around the metal nanoparticles in the first metal particle layer; and the first metal particle layer is arranged close to the quantum dot light-emitting layer, so that when the resonance absorption peak of the metal nanoparticles in the first metal particle layer effectively overlaps with the emission peak of the quantum dots, the radiation recombination rate of the light-emitting layer is significantly increased through effective energy transfer, thereby improving the photoelectric performance of the red, green and blue primary color quantum dot light-emitting devices. In the light-emitting devices of Comparative Examples 1 to 3, the second charge functional layer is directly prepared on the first charge functional layer, and the first charge functional layer does not have a wrinkle structure, resulting in non-radiative recombination of quantum dots, which in turn causes fluorescence attenuation of the quantum dot light-emitting layer, and then leads to poor performance of the light-emitting device. It shows that the present application effectively improves the photoelectric performance of the red, green and blue primary color quantum dot light-emitting devices.
[0179] Obviously, the embodiments described above are only some embodiments of the present application, rather than all embodiments. The preferred embodiments of the present application are given in the accompanying drawings, but they do not limit the patent scope of the present application. The present application can be implemented in many different forms. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive. Although the present application is described in detail with reference to the aforementioned embodiments, for those skilled in the art, it is still possible to modify the technical solutions recorded in the aforementioned specific implementation methods, or to perform equivalent replacement of some of the technical features therein. Any equivalent structure made using the contents of the specification and drawings of this application, directly or indirectly used in other related technical fields, is similarly within the scope of patent protection of this application.
Claims
1. A composite film, characterized in that: include: A first charge functional layer and a first metal particle layer are stacked; The first charge functional layer has a first corrugated structure.
2. The composite film according to claim 1, characterized in that The composite film further comprises a second charge functional layer, wherein the second charge functional layer is arranged on a side of the first metal particle layer away from the first charge functional layer; The first metal particle layer has a second corrugated structure.
3. The composite film according to claim 2, characterized in that: The second charge functional layer has a third corrugated structure, and the first corrugated structure, the second corrugated structure and the third corrugated structure are stacked in sequence.
4. The composite film according to claim 2, characterized in that: The thickness of the second charge functional layer is 5nm-20nm; and / or, The material of the second charge functional layer is selected from poly(9,9-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine), polyvinylcarbazole, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine), 4,4',4"-tri(carbazole-9-yl)triphenylamine, 4,4'-bis(9-carbazole)biphenyl, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-(1 -naphthyl)-1,1'-biphenyl-4,4'-diamine, poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid), 4,4',4'-tri(N-3-methylphenyl-Nphenylamino)triphenylamine, polyaniline, TFB, CuPc, Poly-TPD, DNTPD, TCATA, TCCA, TAPC, MCC, F4-TCNQ, HATCN, Spiro-NPB, Spiro-TPD, transition metal oxides, transition metal sulfides, transition metal tinides, doped graphene, undoped graphene and at least one of C60.
5. The composite film according to any one of claims 1 to 4, characterized in that: The material of the first metal particle layer is selected from one of aluminum and its alloys, copper and its alloys, gold and its alloys, silver and its alloys; and / or, The thickness of the first metal particle layer is 5nm-10nm; and / or, The material of the first charge functional layer is selected from PEDOT:PSS doped with glycerol; and / or, The thickness of the first charge functional layer is 30nm-50nm.
6. A method for preparing a composite film, characterized in that: The method comprises the following steps: providing a preform, the preform comprising a corrugated template and a first charge transport layer; Processing the first charge functional layer by using the corrugated template so that the first charge functional layer has a first corrugated structure; A first metal particle layer is disposed on the first charge functional layer.
7. The method for preparing a composite film according to claim 6, characterized in that: The step of providing a preform, wherein the preform includes a pleated template and a first charge functional layer, specifically comprises: Obtaining a substrate; preparing a polymer template on the substrate; A second metal particle layer is arranged on the polymer template, wherein the second metal particle layer has a different thermal expansion coefficient from the polymer template, so that the second metal particle layer is bent, wherein the material of the second metal particle layer is selected from one of aluminum, titanium, copper, nickel and gold; separating the polymer template having the second metal particle layer from the substrate to obtain a wrinkled template; and / or, The step of using a corrugated template to process the first charge functional layer so that the first charge functional layer has a first corrugated structure specifically includes: The corrugated template is transferred onto the first charge functional layer, so that the first charge functional layer has a first corrugated structure.
8. The method for preparing a composite film according to claim 7, characterized in that: The step of preparing a polymer template on the substrate specifically comprises: Providing a polymer material, and mixing the polymer material with an adhesive in a preset ratio to obtain a mixed solution, wherein the polymer material is at least one of polydimethylsiloxane, polymethyl methacrylate, polyimide, and photoresist; The mixed solution is stirred at a first temperature for a first time, and vacuum dried at room temperature for a second time to discharge bubbles; The mixed solution from which bubbles are expelled is uniformly cast on the substrate, and is cured at a second temperature.
9. A light emitting device, characterized in that: include: A first electrode layer, a second electrode layer, a quantum dot light-emitting layer, and a composite film as claimed in any one of claims 1 to 5; The quantum dot light-emitting layer is arranged between the first electrode layer and the second electrode layer; the composite film is arranged between the first electrode layer and the quantum dot light-emitting layer, and the first metal particle layer is arranged close to the quantum dot light-emitting layer.
10. The light emitting device according to claim 9, characterized in that: The quantum dot light-emitting layer has a fourth wrinkle structure; and / or, The first electrode layer and the second electrode layer are each selected from one or more of a metal electrode, a silicon-carbon electrode, a doped or undoped metal oxide electrode and a composite electrode; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca and Mg; the material of the silicon-carbon electrode is selected from at least one of silicon, graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZ O, MZO and AMO; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or, The material of the quantum dot light-emitting layer includes at least one of a single structure quantum dot and a core-shell structure quantum dot, and the material of the single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, Cd At least one of dZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSS e, SnPbSeTe and SnPbSTe, wherein the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs s, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the core of the quantum dots of the core-shell structure includes any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure includes CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS, ZnS and at least one of the above-mentioned single-structure quantum dots; and / or, The light-emitting device further comprises an electronic functional layer, wherein the electronic functional layer comprises an electron injection layer and / or an electron transport layer. When the electronic functional layer comprises two layers, the electron injection layer and the electron transport layer; the electron transport layer is arranged close to one side of the quantum dot light-emitting layer, and the electron injection layer is arranged away from one side of the quantum dot light-emitting layer; wherein the material of the electron transport layer is selected from at least one of doped inorganic nanocrystals, undoped inorganic nanocrystals, and organic electron transport materials, and the undoped inorganic nanocrystals are selected from ZnO, TiO2, SnO2, Al2O3, GaO, Ga2O3, ZrO2, Fe2O3, CrO3, WO3, CdO, Cu O, MoO2, ZnS, ZnSe, CdS, InP, GaP, LiF, LiF / Yb, MgP, MgF2, Ga2O3, Cs2CO3, Rb2CO3, RbBr; the doped inorganic nanocrystals include a second non-doped inorganic nanocrystal and a doping element, and the second non-doped inorganic nanocrystals are selected from ZnO, TiO2, SnO2, Al2O3, GaO, Ga2O3, ZrO2, Fe2O3, CrO3, WO3, CdO, CuO, MoO2, ZnS, ZnSe, CdS, InP, GaP, LiF, LiF / Yb, MgP, MgF2, G a2O3, Cs2CO3, Rb2CO3, RbBr, the doping element is selected from one or more of Mg, Ca, Li, Ga, Al, Co, Mn; the organic electron transport material is selected from [6,6]-phenyl C71 butyric acid methyl ester, [6,6]-phenyl C61 butyric acid methyl ester, organic fullerene materials, 2-ethyl-1-(4-(10-(2-naphthyl)-9-anthracenyl)phenyl)-1H-benzimidazole, 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 3,3'-[5'-[3-(3-pyridyl)phenyl](TmPyPb), 4,6- Bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine (B3PYMPM), phenylpyridinium beryllium (Bepp2), 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 3-(biphenyl-4-yl)-5-(4-tert-butylphenyl)-4-phenyl-4H-1,2,4-triazole (TAZ), 1,3,5-tri[(3-pyridyl)-3-phenyl]benzene (TmPyPb), tris-(8-hydroxyquinoline)aluminum (Alq3), 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP), 4,7-diphenyl-1,10-phenanthroline (Bphen); The material of the electron injection layer is selected from at least one of LiF, Yb, LiF / Yb, MgP, MgF2, Al2O3, Ga2O3, ZnO, Cs2CO3, Rb2CO3, and RbBr.
11. A display device, characterized in that: It comprises the composite film as claimed in any one of claims 1 to 5, or comprises the composite film prepared by the composite film preparation method as claimed in any one of claims 6 to 8, or comprises the light-emitting device as claimed in any one of claims 9 to 10.